Traveling Mermaids, Traveling Materials: Museum Objects and the Decentering of the Histories of Knowledge - Podgorny, Irina (2024)
This article—which is mostly based on secondary literature following the questions suggested by a visit to the Victoria & Albert Museum—proposes how a decentering of the history of knowledge can be achieved by thinking with museum objects. I chose a particular Leitmotiv, distributed through international trade and scientific networks, which, in the longue durée, brought together a variety of people and connected the most diverse geographies. It follows the itineraries of the Mediterranean mermaid transformed in Latin America into a mermaid musician/guitarist, a character displayed in textiles, ceramics, and furniture and which is featured today in collections of popular culture, ethnography, and decorative arts. Using this example, this paper explores the cross-cultural transfers that shaped and cross-linked cultures to remind us that such objects were the result of multiple exchanges happening in several places and that, to understand them, historians have to cross national and disciplinary borders, languages, and, finally, those chronological periods that make us forget the centrality to history of change and continuity.